2016
DOI: 10.3389/fnins.2016.00523
|View full text |Cite
|
Sign up to set email alerts
|

Oct4 Methylation-Mediated Silencing As an Epigenetic Barrier Preventing Müller Glia Dedifferentiation in a Murine Model of Retinal Injury

Abstract: Müller glia (MG) is the most abundant glial type in the vertebrate retina. Among its many functions, it is capable of responding to injury by dedifferentiating, proliferating, and differentiating into every cell types lost to damage. This regenerative ability is notoriously absent in mammals. We have previously reported that cultured mammalian MG undergoes a partial dedifferentiation, but fails to fully acquire a progenitor phenotype and differentiate into neurons. This might be explained by a mnemonic mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…We speculate that this upregulation is due to epigenetic modifications of the sox2 locus. A recent study in the mouse retina showed that the expression of oct4 is upregulated shortly after injury and then downregulated at 24 hpi ( Reyes-Aguirre and Lamas, 2016 ). This correlates with a decrease in the expression of DNA methyltransferase 3b and its subsequent upregulation at 24 hpi, triggering a decrease in methylation and subsequent re-methylation of oct4 .…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this upregulation is due to epigenetic modifications of the sox2 locus. A recent study in the mouse retina showed that the expression of oct4 is upregulated shortly after injury and then downregulated at 24 hpi ( Reyes-Aguirre and Lamas, 2016 ). This correlates with a decrease in the expression of DNA methyltransferase 3b and its subsequent upregulation at 24 hpi, triggering a decrease in methylation and subsequent re-methylation of oct4 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that mammalian retinas become enriched with quiescent MGCs, so they fail to renew neurons. In this sense, studies in zebrafish have proved extremely useful for determining the master regulators of this complex process; therefore, further investigations are now being focused on the modulation of these proteins in mammalian or avian retinas to stimulate MGC reprogramming (Beach, Wang, & Otteson, ; Reyes‐Aguirre & Lamas, ). Thus, inducing changes in the expression of certain proteins or epigenetic modifications is considered to be a possible therapy for restoring the pool of neurons in the retina.…”
Section: Gliosismentioning
confidence: 99%
“…Hdac1 being part of multi-protein nuclear complexes that are important for causing transcriptional repression and epigenetic landscaping to inhibit the expression of neuronal-specific genes in rest of the tissues ( Huang et al., 1999 ) made us explore the global gene regulations that occur in MGPCs mediated through Hdacs with a particular focus on Hdac1. Furthermore, MG reprogramming leading to induction of MGPCs, with little neuronal characteristics, during retina regeneration is associated with essential expression of pluripotency-inducing factors ( Gorsuch et al., 2017 , Ramachandran et al., 2010a , Reyes-Aguirre and Lamas, 2016 ), which could also be targets of epigenome modifiers like Hdacs.…”
Section: Introductionmentioning
confidence: 99%